2013
DOI: 10.1002/atr.1242
|View full text |Cite
|
Sign up to set email alerts
|

Modelling heavy vehicle car‐following behaviour in congested traffic conditions

Abstract: SUMMARY This study develops a car‐following model in which heavy vehicle behaviour is predicted separately from passenger car. Heavy vehicles have different characteristics and manoeuvrability compared with passenger cars. These differences could create problems in freeway operations and safety under congested traffic conditions (level of service E and F) particularly when there is high proportion of heavy vehicles. With increasing numbers of heavy vehicles in the traffic stream, model estimates of the traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 22 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Higher ACG percent would waste vehicle energy directly. As shown in (17) to (19), ACG percent is defined as two aspects: (1) drivers pressed the acceleration pedal but the gear is zero or (2) acceleration pedal is pressed and the pedal travel of clutch is equal to or more than 2/3 at the same time.…”
Section: ) Standard Deviation Of Acceleration Pedal Applying Value (mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher ACG percent would waste vehicle energy directly. As shown in (17) to (19), ACG percent is defined as two aspects: (1) drivers pressed the acceleration pedal but the gear is zero or (2) acceleration pedal is pressed and the pedal travel of clutch is equal to or more than 2/3 at the same time.…”
Section: ) Standard Deviation Of Acceleration Pedal Applying Value (mentioning
confidence: 99%
“…Hence, aiming at reliability prediction and evaluation, the method based on artificial neural network would be better. Among these artificial neural networks, backpropagation (BP) neural network is the most commonly used, especially in practical application [17,18]. Moreover, BP network has apparent advantages in self-learning, selforganizing, good fault tolerance, and excellent nonlinear approximation ability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many specialized studies have investigated the road running characteristics attributable to large vehicles. Related research mainly analyzed the bottleneck effect of large vehicles from the microscopic theory and obtained some generally accepted conclusions [4][5][6][7][8][9][10][11]. In 1992, Gazis and Herman [4] proposed a mobile bottleneck concept for vehicle queuing caused by slow vehicles on low-speed roads and proposed a mobile bottleneck model for symmetric lane changing in two-lane highways.…”
Section: Introductionmentioning
confidence: 99%
“…At a sufficiently high truck mixing rate, the traffic speed approaches a certain fixed speed, which is related to the expected speed of the truck. Some scholars have studied the dynamics of heavy vehicle interactions in car following [8][9][10][11][12]. By simulating the behavior of following in the congested traffic conditions and the lane changing operation of heavy vehicles, it was found that the existence of heavy vehicles will lead to larger space and time headways, longer reaction time, and more robust car-following behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of his research show the complication of acceleration/deceleration of heavy freight vehicles causes larger space and time headways when traffic flow approaches capacity. Besides, heavy freight vehicles intend to keep a stable speed when following and the reaction time of different drivers' changes less obviously [21]. Yang et al [22] used cellular automation to simulate the car-following behaviors of heavy freight vehicles when following passenger cars, which indicates that car-following behaviors between heavy freight vehicles and passenger cars will exert different impact on traffic capacity if traffic flow state changes.…”
Section: Introductionmentioning
confidence: 99%